The impact of the use of gamification on the development of creative thinking skills among students of the basic third grade in the subject of Science in the capital Amman - Al-Nadi, Huda Gumaa (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to investigate the Effect of using Gamification on developing creative thinking skills for third-grader students in basic Science in the capital of Amman, To achieve this aim, It used the semi-experimental method, and conducted the Torrance test for creative thinking (in the verbal) form (a) developed after it was of his Validity and Reliability on a sample of (134) male and female students randomly distributed to two groups, an experimental group who studied gamification consisting of (68) male and female students. And a control group studied in the normal method consisting of (66) male and female students, and the study found that there are statistical differences in overall performance and in each skill in testing the skills of creative dimensional thinking in favor of the experimental group, The study recommended several recommendations, the most important one is benefiting from gamification in developing creative thinking skills for third grade students in Amman, The second semester of the academic year 2019/2020, The researcher recommended using gamification in teaching science subjects, specifically in the development of creative thinking skills: (fluency, flexibility, originality).
Keywords: Gamification; Creative thinking skills; Science Subject